Spiritual health status in students of Shahid Beheshti University and Shahid Beheshti University of Medical Sciences - Sima Marzban; Akbar Babaei Heydarabadi; Ebrahim Rahimi; Marjan Vejdani; Moslem Shokri (Shahid Beheshti University of Medical Sciences, 2016)
For downloading the full-text of this article please click here Background and Objectives: Spiritual health is one of the aspects of human health, in addition to physical, mental and social health and causes the integrated relationship among internal forces. The aim of this study is determination of the spiritual health status in Students of Shahid Beheshti University and Shahid Beheshti University. Materials and Methods: This study was a cross-sectional and descriptive - analytic that conducted on 367 students in 2015. The sampling method was quota sampling. Data were collected using valid and reliable measure of spiritual health questionnaire with 48 questions, in the form of two components of cognitive-emotional (insight and orientation) and behavior; and three concept of relationship with God, with oneself and around. The data were analyzed with software SPSS21. Results: From 367 participants in the study, 59.1 percent were tempfemale and 12.3 percent were married and 66.4 percent of them lived in Tehran. 47.2% of participants were studying for BS and the rest in graduate and PhD. The mean age (standard deviation) ) was reported 22.64 (3.88). The mean (SD) of insight and spiritual orientation, behavior and spiritual health were 79.94 (15.34) 71.96 (14.28) and 76.62 (13.89), respectively. Conclusion: The mean scores of students were relatively high in the field of vision and spiritual orientation, moral behavior and spiritual health. The average of spiritual health indicators and its performance was more in girls and married students than boys and unmarried. As well as there was a significant relationship between spiritual insight  and orientation with behavior. Keywords: Spiritual Health, Religious, Students For downloading the full-text of this article please click here